Question: 2 x 3 x 4 Answer: It's easier to break this down into separate parts. First, multiply 2 x 3 = 6 Then multiply 6 (which is 2 x 3) x 4 = 24 Therefore, 2 x 3 x 4 = 24
1/4 x 3 = (1x3) / 4 = 3/4
To find 3 x 2 x 4, you can multiply the numbers sequentially: first, multiply 3 and 2 to get 6, then multiply the result by 4 to get 24. Another method is to use the distributive property: 3 x (2 x 4) = 3 x 8 = 24. Lastly, you can use the commutative property to rearrange the numbers: 3 x 2 x 4 = 2 x 3 x 4 = 2 x 12 = 24.
144
You multiply 1 x 2. Then you multiply the result with the next number: 2 x 3 = 6. Then you multiply the result with the next number: 6 x 4 = 24. You continue, until you have multiplied all the numbers.You multiply 1 x 2. Then you multiply the result with the next number: 2 x 3 = 6. Then you multiply the result with the next number: 6 x 4 = 24. You continue, until you have multiplied all the numbers.You multiply 1 x 2. Then you multiply the result with the next number: 2 x 3 = 6. Then you multiply the result with the next number: 6 x 4 = 24. You continue, until you have multiplied all the numbers.You multiply 1 x 2. Then you multiply the result with the next number: 2 x 3 = 6. Then you multiply the result with the next number: 6 x 4 = 24. You continue, until you have multiplied all the numbers.
(x+3)(x+4) = x2+7x+12
To find an equation where two numbers are solutions of x, do the following: x=-3 , x=4 x+3=0 , x-4=0 Multiply them together and set equal to zero, i.e. (x+3)(x-4) = x2-x-12 = 0
Question: 2 x 3 x 4 Answer: It's easier to break this down into separate parts. First, multiply 2 x 3 = 6 Then multiply 6 (which is 2 x 3) x 4 = 24 Therefore, 2 x 3 x 4 = 24
You can get ten using 5,4,3,2 by the following equation: (5 x 2)(4 - 3).
(x+3)(x+4)=x2+7x+12
12
12
3 x 3 x 3 x 5 = 135
1/4 x 3 = (1x3) / 4 = 3/4
To find 3 x 2 x 4, you can multiply the numbers sequentially: first, multiply 3 and 2 to get 6, then multiply the result by 4 to get 24. Another method is to use the distributive property: 3 x (2 x 4) = 3 x 8 = 24. Lastly, you can use the commutative property to rearrange the numbers: 3 x 2 x 4 = 2 x 3 x 4 = 2 x 12 = 24.
-4 x -3 = 12
6 / ( x + 4 ) = 2 / 3 1 - Multiply both parts by 3 3 * 6 / ( x + 4 ) = 2 2- Multiply both parts by (x+4) 3 * 6 = 2 * ( x + 4 ) 3 - Simplify 18 = 2x + 8 10 = 2x 5 = x